Pelatihan Komputer dan Bedah Soal Persiapan ANBK Kelas V SDN 02 Pariangan - Ana Nurul Falah Ana; Annisa Rizky Eristia; Sunarti (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This service is motivated by the implementation of the Computer-Based National Assessment (ANBK) in elementary schools. The implementation of ANBK at the elementary school level requires a lot of preparation, one of which is preparing students who are not yet familiar with computers to take part in the Computer-based Assessment. The aim of this service is to introduce students to computers in general and increase understanding regarding ANBK materials. The service is carried out using a Participatory Action Research (PAR) approach, which is carried out in the form of computer introduction activities, getting used to typing in a word processing application (Microsoft Word), in-depth study of material and question analysis, as well as ANBK simulations. The service is carried out in collaboration between the service team and the school operator or admin. The training participants were class V students at SDN 02 Pariangan, totaling 27 people. This service is able to provide understanding and knowledge that students can implement in the ANBK system on computers. This can be seen from students who have increased understanding regarding computer basics, are fluent in typing personal identity, understand ANBK material, and are able to complete ANBK simulations well.